Highly Stable Porous Polyimide Sponge as a Separator for Lithium-Metal Secondary Batteries - Junyoung Choi; Kwansoo Yang; Hyeon-Su Bae; Isheunesu Phiri; Hyun Jeong Ahn; Jong Chan Won; Yong Min Lee; Yun Ho Kim; Myung-Hyun Ryou (Nanomaterials, 2020)
To inhibit Li-dendrite growth on lithium (Li)-metal electrodes, which causes capacity deterioration and safety issues in Li-ion batteries, we prepared a porous polyimide (PI) sponge using a solution-processable high internal-phase emulsion technique with a water-soluble PI precursor solution; the process is not only simple but also environmentally friendly. The prepared PI sponge was processed into porous PI separators and used for Li-metal electrodes. The physical properties (e.g., thermal stability, liquid electrolyte uptake, and ionic conductivity) of the porous PI separators and their effect on the Li-metal anodes (e.g., self-discharge and open-circuit voltage properties after storage, cycle performance, rate capability, and morphological changes) were investigated. Owing to the thermally stable properties of the PI polymer, the porous PI separators demonstrated no dimensional changes up to 180 °C. In comparison with commercialized polyethylene (PE) separators, the porous PI separators exhibited improved wetting ability for liquid electrolytes; thus, the latter improved not only the physical properties (e.g., improved the electrolyte uptake and ionic conductivity) but also the electrochemical properties of Li-metal electrodes (e.g., maintained stable self-discharge capacity and open-circuit voltage features after storage and improved the cycle performance and rate capability) in comparison with PE separators.